A Palmitoylethanolamide Producing Lactobacillus paracasei Improves Clostridium difficile Toxin A-Induced Colitis - Esposito, Giuseppe; Corpetti, Chiara; Pesce, Marcella; Seguella, Luisa; Annunziata, Giuseppe; Del Re, Alessandro; Vincenzi, Martina; Lattanzi, Roberta; Lu, Jie; Sanseverino, Walter; Sarnelli, Giovanni (Frontiers in Pharmacology, 2021)
Genetically engineered probiotics, able to in situ deliver therapeutically-active compounds while restoring gut eubiosis, could represent an attractive therapeutic alternative in Clostridium difficile infection (CDI). Palmitoylethanolamide (PEA) is an endogenous lipid able to exert immunomodulatory activities and restore epithelial barrier integrity in human models of colitis, by binding the peroxisome proliferator-activated receptor-α (PPARα). The aim of this study was to explore the efficacy of a newly designed PEA-producing probiotic (pNAPE-LP) in a mice model of C. difficile toxin A (TcdA)-induced colitis. The human N-acyl-phosphatidylethanolamine-specific phospholipase D (NAPE-PLD), a key enzyme involved in the synthesis of PEA, was cloned and expressed in a Lactobacillus paracasei, that was intragastrically administered to mice 7 days prior the induction of the colitis. Bacteria carrying the empty vector served as negative controls (pLP). In the presence of palmitate, pNAPE-LP was able to significantly increase PEA production by 27900%, in a time- and concentration-dependent fashion. Mice treated with pNAPE-LP showed a significant improvement of colitis in terms of histological damage score, macrophage count and myeloperoxidase levels (-53, -82% and -70.4%, respectively). This was paralleled by a significant decrease both in the expression of Toll Like Receptor-4 (-71%), phospho-p38 Mitogen-activated protein kinase (-72%), Hypoxia-inducible factor-1-alpha (-53%), p50 (-74%) and p65 (-60%) and in the plasmatic levels of Interleukin 6 (-86%), nitric oxide (-59%) and Vascular-Endothelial Growth Factor (-71%). Finally, tight junction protein expression was significantly improved by pNAPE-LP treatment as witnessed by the rescue of Zonula Occludens-1 (+304%), Ras homolog family member A-GTP (+649%) and occludin expression (+160%). These protective effects were mediated by the specific release of PEA by the engineered probiotic, as they were abolished in PPARα knock-out mice and in wild type mice treated with pLP. Herein, we demonstrated that pNAPE-LP has therapeutic potential in CDI by inhibiting colonic inflammation and restoring tight junction protein expression in mice, paving the way to next generation probiotics as a promising strategy in CDI prevention.